Predictors of short-term anxiety outcome in subthalamic stimulation for Parkinson’s disease - Anna Sauerbier; Johanna Herberg; Vasilija Stopic; Philipp A. Loehrer; Keyoumars Ashkan; Alexandra Rizos; Stefanie T. Jost; Jan Niklas Petry-Schmelzer; Alexandra Gronostay; Christian Schneider; Veerle Visser-Vandewalle; Julian Evans; et al. (npj Parkinson's Disease, 2024)
Abstract The effects of subthalamic nucleus deep brain stimulation (STN-DBS) on anxiety in Parkinson’s disease (PD) are understudied. We identified clinical predictors of STN-DBS effects on anxiety in this study. In this prospective, open-label, multicentre study, we assessed patients with anxiety undergoing STN-DBS for PD preoperatively and at 6-month follow-up postoperatively. We assessed the Hospital Anxiety and Depression Scale (HADS-anxiety and depression subscales), Unified PD Rating Scale-motor examination, Scales for Outcomes in PD-motor (SCOPA-M)-activities of daily living (ADL) and -motor complications, Non-Motor Symptom Scale (NMSS), PDQuestionnaire-8 (PDQ-8), and levodopa-equivalent daily dose. We tested changes at follow-up with Wilcoxon signed-rank test and corrected for multiple comparisons (Bonferroni method). We identified patients with a clinically relevant anxiety improvement of anxiety based on a designated threshold of ½ standard deviation of baseline HADS-anxiety. Moreover, we investigated predictors of HADS-anxiety changes with correlations and linear regressions. We included 50 patients with clinically relevant baseline anxiety (i.e., HADS-anxiety ≥ 8) aged 63.1 years ± 8.3 with 10.4 years ± 4.5 PD duration. HADS-anxiety improved significantly at 6-month follow-up as 80% of our cohort experienced clinically relevant anxiety improvement. In predictor analyses, worse baseline SCOPA-ADL and NMSS-urinary domain were associated with greater HADS-anxiety improvements. HADS-anxiety and PDQ-8 changes correlated moderately. Worse preoperative ADL and urinary symptoms predicted favourable postoperative anxiety outcome, which in turn was directly proportionate to greater QoL improvement. This study highlights the importance of detailed anxiety assessments alongside other non-motor and motor symptoms when advising and monitoring patients undergoing STN-DBS for PD.